Price Discrimination in Input Markets: Quantity Discounts and Private Information - Fabian Herweg; Daniel Müller (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2011)
We consider a monopolistic supplier's optimal choice of wholesale tariffs when downstream firms are privately informed about their retail costs. Under discriminatory pricing, downstream firms that differ in their ex ante distribution of retail costs are offered different tariffs. Under uniform pricing, the same wholesale tariff is offered to all downstream firms. In contrast to the extant literature on thirddegree price discrimination with nonlinear wholesale tariffs, we find that banning discriminatory wholesale contracts—the usual legal practice in the EU and US— often is beneficial for social welfare. This result is shown to be robust even when the upstream supplier faces competition in the form of fringe supply.
urn:nbn:de:bvb:19-epub-12414-4
Keywords: D43; L11; L42; 330; Asymmetric Information; InputMarkets; Quantity Discounts; Price Discrimination; Screening; Vertical Contracting; Lieferantenmanagement; Preisdifferenzierung; Vorleistungen; Markteintritt; Marktstruktur; Wohlfahrtsanalyse; Theorie